2005
DOI: 10.1172/jci24301
|View full text |Cite
|
Sign up to set email alerts
|

PI3K integrates the action of insulin and leptin on hypothalamic neurons

Abstract: Central control of energy balance depends on the ability of proopiomelanocortin (POMC) or agouti-related protein (Agrp) hypothalamic neurons to sense and respond to changes in peripheral energy stores. Leptin and insulin have been implicated as circulating indicators of adiposity, but it is not clear how changes in their levels are perceived or integrated by individual neuronal subtypes. We developed mice in which a fluorescent reporter for PI3K activity is targeted to either Agrp or POMC neurons and used 2-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
227
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(252 citation statements)
references
References 53 publications
11
227
0
14
Order By: Relevance
“…Deletion of both subunits disrupts the acute effects of leptin and insulin in resting membrane potential of hypothalamic LR neurons (6,17). However, the physiological consequences of this manipulation have not been determined.…”
Section: Mice With Deletion Of Pi3k Signaling Pathway In Lr Cells Havmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of both subunits disrupts the acute effects of leptin and insulin in resting membrane potential of hypothalamic LR neurons (6,17). However, the physiological consequences of this manipulation have not been determined.…”
Section: Mice With Deletion Of Pi3k Signaling Pathway In Lr Cells Havmentioning
confidence: 99%
“…Phosphatidylinositol 3-kinase (PI3K) signaling is the major molecular pathway associated with these diseases and comorbidities (1)(2)(3). It plays a key role in the central actions of metabolic cues and growth factors in energy balance, glucose homeostasis, and cellular growth (4)(5)(6)(7)(8). Among the multiple PI3K isoforms, those pertaining to class IA are responsive to metabolic signals (9).…”
Section: Introductionmentioning
confidence: 99%
“…We set out to investigate the metabolic phenotypes mediated by SOCS3 up-regulation in AgRP neurons. Mice carrying a Cre-activatable allele of wild-type Socs3 (6) were crossed with mice expressing Cre recombinase specifically in the AgRP neurons (24), such that SOCS3 would be overexpressed specifically in the AgRP neurons. We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6).…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…Both leptin and insulin activate PI3Kinase (via insulin receptor substrate) that leads to the metabolism of phosphatidylinositol (4.5) biphosphate (PIP 2 ) to phoshatidylinositol (3,4,5)-triphosphate (PIP 3 ) in POMC neurons (Xu et al, 2005). Activation of GIRK channels requires permissive levels of membrane PIP 2 and increased channel activity results from Gβγ-mediated stabilization of PIP 2 -GIRK binding (Huang et al, 1998, Zhang et al, 1999.…”
Section: Effects Of 17β -Estradiol On Vmh and Arcuate Neurons: Role Imentioning
confidence: 99%